Analysis of Marketing Tools Use by e-Administration in Poland - Aleksandra MAKOWSKA (Communications of International Proceedings, 2021)
The purpose of this article is to identify and indicate the scope of using 5P marketing tools by e-government in Poland. This analysis will show the strengths and weaknesses of the system. Empirical research conducted in the form of a case study of the activities of portals offering e-administration services in Poland and cases of specific services were devoted to the execution of the aim of the work. The proposed products, their price, distribution, promotion and preparation of administration employees to work in the electronic system were analysed. Statistical data available on government websites and data from the European Union were also used for this purpose.
Keywords: E-Administration; E-Government; Marketing Tools